Violencia estudiantil y su influencia en el entorno socio afectivo de un estudiante de la Unidad Educativa Jorge Icaza Delgado - Reina Sandoya, Leonor Elizabeth (2020)
Student violence is a fact involving victims, aggressors and observers, these three elements give direct way to this educational social phenomenon of which in large part, they do not know the affective socio-consequences that result from such act taken as a simple act of pleasure on the part of the victims. So this research, beyond being considered a step prior to obtaining a higher degree, aims to develop strategies and indicators that warn about the execution of this bad practice, which will allow anyone to detect the condition of their children or those close to them, since it has factors of easy detection , by using the right tools, such as appreciating whether the child has changes in their behavior, reduces their academic performance and so on. Already addressing the space of his emotional intelligence, within this research we will find a case analysis of a minor of the Jorge Icaza Delgado Educational Unit of the city of Babahoyo, who suffered the problem addressed; the same as through the application of the techniques provided to us by clinical psychology was able to detect the condition noted, being used in the clinical observation and application of the respective tests, concluding that there is a direct relationship between school violence and affective socio-development in students, in a negative way.